Hospital-Based Observational Study of Mucocutaneous Adverse Reactions of Tyrosine Kinase Inhibitors - Gowda, Sona C.; Noronha, Tonita Mariola; Shetty, Vijith (Indian Journal of Medical and Paediatric Oncology, 2025)
Tyrosine kinase inhibitors (TKIs), although considered less toxic than conventional chemotherapy, are not short of adverse drug reactions (ADRs). Cutaneous toxicities are among the most frequently reported ADRs; when severe, they can cause substantial morbidity, often requiring dose reduction or drug cessation.1. To estimate the frequency and pattern of mucocutaneous adverse reactions of TKI. 2. To grade the adverse reactions based on the severity scale of CTCAE v 5.0.This was a hospital-based observational study of 105 patients on TKI chemotherapy, attending the outpatient departments of dermatology and medical oncology, at Justice K.S. Hegde Charitable Hospital, Mangalore, from October 1, 2022, to April 30, 2024. Mucocutaneous adverse reactions after the initiation of TKI were recorded and graded according to the severity scale of CTCAE v 5.0. and causality was assessed using WHO-UMC criteria.Among 105 patients, a majority of 34 (32.4%) patients belonged to the age group of 51 to 60 years, with a male predominance of 2:1. The most frequent cancer was lung in 38 (36.2%) patients, followed by CML in 21 (20.0%) patients. The most common class of TKI agent used was EGFR inhibitors in 51 (48.6%) patients, with gefitinib being the most common TKI agent in 46 (43.8%) patients. The most frequently reported ADRs were xerosis in 45 (42.9%) patients, followed by eczematous changes in 37 (35.2%) patients. The papulopustular rash was most commonly seen with EGFR inhibitors in 25 (49.0%) patients, eczematous changes with BCR–ABL inhibitors in 14 (50.0%), and hand–foot skin reaction with multikinase inhibitors in 12 (54.4%) patients. A statistically significant association was noted between papulopustular rash and paronychia among patients on EGFR inhibitors. Additionally, a statistically significant association was noted between hand–foot skin reaction and subsequent dose reduction.An awareness regarding the various ADRs of TKIs and interdisciplinary cooperation between oncologists and dermatologists will help in precise diagnosis and early identification of various cutaneous toxicities.
Keywords: adverse drug reactions; tyrosine kinase inhibitors; EGFR inhibitors; targeted chemotherapy